PENGARUH KOREAN WAVE, WORD OF MOUTH DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN: (Studi Pada Konsumen Produk Kosmetik Korea Romand Indonesia di Jakarta Selatan) - Nierma Restha; Ravindra Safitra Hidayat (Jurnal Ilmiah Manajemen dan Akuntansi, 2024)
This research aims to determine the influence of the Korean Wave, Word of Mouth, and Brand Image on Purchase Decisions among consumers of Romand Korea Cosmetic Products in South Jakarta, Indonesia. This research is of a quantitative type. The population of the study consists of 800 individuals. The sample used includes 127 respondents, selected using a non-probability sampling technique with an accidental sampling method. Data collection was done through a questionnaire with a Likert scale that was processed using SPSS Version 22 software. The data analysis involved validity and reliability tests, classical assumption tests, hypothesis testing, and multiple linear regression. The results of this study indicate that the variables Korean Wave, Word of Mouth, and Brand Image each have a significant influence on Purchase Decisions.